Skipping ahead: A circuit for representing the past, present, and future - Robinson, Jennifer C; Brandon, Mark P (eLife, 2021)
Envisioning the future is intuitively linked to our ability to remember the past. Within the memory system, substantial work has demonstrated the involvement of the prefrontal cortex and the hippocampus in representing the past and present. Recent data shows that both the prefrontal cortex and the hippocampus encode future trajectories, which are segregated in time by alternating cycles of the theta rhythm. Here, we discuss how information is temporally organized by these brain regions supported by the medial septum, nucleus reuniens, and parahippocampal regions. Finally, we highlight a brain circuit that we predict is essential for the temporal segregation of future scenarios.
Keywords: hippocampus; prefrontal cortex; cycle skipping; memory; theta sequences